Religious Ethics in the Market Economy A New Approach to Business and Morality - Jechoutek, Karl G. (Humanism in Business Series, 2018)
This book aims to go beyond merely confrontational or complementary treatments of the relationship between market participation and business ethics. Reviewing the attitudes towards the market embedded in religious ethics and scholars, it explores the symbiotic relationship between the economy, ethics and morals. Moving the discussion beyond a static and traditional economy envisaged by scripture, it explores the impact of an evolving and globalised economy based on the value systems of moral philosophy and religious ethics. The Author aims to expand the conventional view of business ethics, encouraging readers to interpret markets and morality as intertwined concepts, and use them to inform further research. .